Optimising capsicum chinense growth in cocopeat media: the effects of pineapple leaf biochar and trichoderma biofertiliser - Mahdian, Suraiya; Mohidin, Hasmah; Abdullah, Rosazlin; Khalid, Khadijah; Basri, Saiyidah Raffhanah; Jos, Syahira; Rosli, Nurmaliena (Universiti Teknologi MARA, Sarawak, 2025)
The escalating demand for pineapples has led to a proportional increase in pineapple leaf waste, posing environmental challenges if not effectively managed. Numerous studies have explored the conversion of pineapple leaf waste into biochar to improve soil fertility. However, research on using pineapple leaf biochar (PLB) in cocopeat remains limited. Therefore, this study examines the effect of PLB and Trichoderma biofertiliser (TBF) on the growth, yield, and nutrient content of the Capsicum chinense plant grown in cocopeat media. Seven treatment groups were established: T0 = Control, T1 = Commercial organic fertiliser, T2 = 100% PLB, T3 = 100% TBF, T4 = 75% PLB + 25% TBF, T5 = 50% PLB + 50% TBF, and T6 = 25% PLB + 75% TBF. The C. chinense was planted in a polybag filled with cocopeat, placed in a rain shelter, and equipped with a fertigation system. The parameters measured included plant growth, yield, and nutrient content. Destructive sampling was done five months after treatment. The findings showed T4 emerged as an alternative to chemical fertiliser, as the results were comparable to T0 which helped boost plant growth, yield (403.69 g), biomass (156.13 g), and nutrient uptake (N: 9.33%, P: 1.68%, K: 13.20%) of C. chinense plant. Therefore, T4 is recommended as an organic amendment for cocopeat media.